Nitrogen Vacancy‐Induced Deposition of Pd Nanoparticles onto g‐C3N4 with Greatly Improved Photocatalytic Activity in H2 Evolution. Issue 7 (15th April 2021) - Yao, Yuan; Ren, Guangmin; Li, Zizhen; Bai, Hongcun; Hu, Xiude; Meng, Xiangchao
Abstract : C3 N4 exhibits excellence in photocatalytic water splitting. However, some hindrances should be overcome before its wide application. Herein, nitrogen vacancies (NVs) are successfully introduced in C3 N4 . As‐fabricated NVs act as targets to induce the deposition of Pd nanoparticles (NPs). Photocatalytic activity in H2 evolution for C3 N4 is improved from none to 10.12 μmol h −1 gcat −1 in the presence of NVs, and to 287.94 μmol h −1 gcat −1 with the modifications of both NVs and Pd NPs. The great improvement may be due to that: 1) the formation of NVs can drive up the Fermi level and optimize the band structure of C3 N4 ; 2) the addition of the impure energy level of NV within the bandgap expands the utilization of the solar spectrum; 3) Pd NPs with the surface plasmonic resonance (SPR) effect are capable of absorbing more visible‐light photons; and 4) Pd acts as a reservoir of photogenerated charge carriers, suppressing its recombination. The mechanism of the enhancements is explored in detail and comprehensively discussed in this work. Abstract : Nitrogen vacancies (NVs) induce the deposition of Pd nanoparticles (NPs) onto C3 N4 . The well‐dispersed Pd NPs and the unoccupied NVs act as reactive sites and synergistically enhance the photocatalytic activity of C3 N4 in H2 evolution. This work provides not only a new approach to load metallic NPs, but also a new strategy to improve the photocatalytic activity.